Kinerja Bisnis Agroindustri Pengolahan Ikan Di Jawa Timur - Sulaefi, Sulaefi (Jurnal Bisnis Teori & Implementasi)
The Business of Agroindustry in East Java relies its comparative advantages, which include the low cost of raw material and labor. Meanwhile, its competitive advantages, which determine the competitiveness of the product in a free market. Still need to be developed.Â The competitiveness of the agroindustry particulary those run by small and medium businesses are relatively weak since most of agroindustry are facing thr problem of product quality that does not conform the quality standard. This problem arises due to insufficient use of technology, low skill human resource involved in production activity, low funding, low marketing effort, and low institutional support. The development of agrohindustry in East Java must be directed to some basic aspects of agroindustry that include: the development of human resources, the improvement of process technology, the strengthening of marketing network, the improvement of funding and investment structure, and the establishment of appropriate institution.Â